Konsistensi Sayyid Qutb terhadap Corak Al Adabiy wal Ijtima’iy dan Dakwah wal Harakah - Nur, Afrizal (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2021)
The activity of interpreting the Qur'an from the time of the Prophet to this day is still ongoing.However, the miracle of the Qur'an remains lasting and is increasingly interesting to study, because the Qur'an is the main source of law, a source of knowledge and a source of human guidance that is not timeless by heat and is not weathered by rain. The dynamics of the methodology of interpretation always occur, including the dynamics of the style and orientation of the interpretation of the Qur'an which arise as a response to the social conditions of the community and the ummah, so that the material for interpretation is more dominant in the form of da'wah messages and movements. Receptions of Orientation and Interpretation Patterns Current contemporary in modern tafseer books are al da'wah wal Harakah, al adabiy ijtimaiy, and Ilmi styles. The al-Dakwah wal Harakah style is an interpretive style whose focus is to convey the verses of the Koran with the packaging of da'wah with all forms of conceptual movement strategies, namely full of wisdom, good teaching, and performing mujadalah as the best step, so that Congratulations, the ummah from practices of deviating aqidah, worship and deviation in mu'amalah, so that people who are istiqamah in faith will emerge from the darkness and practice of modern ignorance into the light of Islam which guarantees physical happiness and inner happiness in the world and the hereafter.